2020
DOI: 10.3310/hsdr08360
|View full text |Cite
|
Sign up to set email alerts
|

Immediate versus delayed short-term integrated palliative care for advanced long-term neurological conditions: the OPTCARE Neuro RCT

Abstract: Background Palliative care is recommended to help meet the needs of patients with progressive non-cancer conditions, such as long-term neurological conditions. However, few trials have tested palliative care in this population. Objectives To determine the effectiveness and cost-effectiveness of short-term integrated palliative care in improving symptoms, improving patient- and caregiver-reported outcomes and reducing hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 84 publications
(101 reference statements)
0
15
0
Order By: Relevance
“…Another RCT published results and analyses in 2 different publications. 25,34 Three Cochrane review [14][15][16] and 1 systematic review 17 were also identified and screened for any additional RCTs. One RCT 22 met this review's inclusion/exclusion criteria, yielding a total of 5 RCTs for qualitative synthesis.…”
Section: Study Selectionmentioning
confidence: 99%
See 4 more Smart Citations
“…Another RCT published results and analyses in 2 different publications. 25,34 Three Cochrane review [14][15][16] and 1 systematic review 17 were also identified and screened for any additional RCTs. One RCT 22 met this review's inclusion/exclusion criteria, yielding a total of 5 RCTs for qualitative synthesis.…”
Section: Study Selectionmentioning
confidence: 99%
“…Of the 3 phase II RCTs, 2 enrolled people living with MS and their caregivers (in London, England and 3 locations in Italy, respectively) and the third enrolled people living with MS, motor neuron disease or a movement disorder and their caregivers in Turin, Italy. 30,21,22,23 Of the 2 phase III trials; 24,25,34 there was a pragmatic design study investigating an outpatient integrated palliative care model of delivering PCI in an outpatient movement disorder clinic setting at 3 different academic centers ( 2 in the United States and 1 in Canada). 24 and the other investigated specialty palliative care delivered as a brief, targeted PCI in the outpatient setting for patients and their caregivers already receiving primary medical and specialty neurologic care for MS, motor neuron disease or a movement disorder at one of 7 different sites across the United Kingdom.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations